2013
DOI: 10.1007/s12032-013-0475-1
|View full text |Cite
|
Sign up to set email alerts
|

High expression of LC3B is associated with progression and poor outcome in triple-negative breast cancer

Abstract: Microtubule-associated protein 1 light chain 3B (LC3B) was involved in autophagosome formation and had been as a marker of autophagy which played an important role in the development of breast cancer. The purpose of this study was to explore the level of LC3B expression in four stages of triple-negative breast cancer (TNBC) and to evaluate the prognostic significance of LC3B expression in TNBC. The ultimate aim was to identify the new factor that could be useful in predicting clinical behavior of TNBC. We eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
69
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(79 citation statements)
references
References 27 publications
6
69
1
Order By: Relevance
“…27,30 In a cohort of patients with locally advanced BC that received neoadjuvant chemotherapy, a high intensity of LC3B staining was described as a (negative) independent prognostic factor for relapse-free and overall survival, 27 in particular in triple-negative cancers. 31 A recent meta-analysis confirmed that high expression of LC3B predicts adverse OS in BC. 32 However, none of the aforementioned studies was based on the quantification of LC3B C puncta, and rather scored the overall expression level of LC3B, meaning that the evaluation criteria was rather different from those reported here.…”
Section: Discussionmentioning
confidence: 93%
“…27,30 In a cohort of patients with locally advanced BC that received neoadjuvant chemotherapy, a high intensity of LC3B staining was described as a (negative) independent prognostic factor for relapse-free and overall survival, 27 in particular in triple-negative cancers. 31 A recent meta-analysis confirmed that high expression of LC3B predicts adverse OS in BC. 32 However, none of the aforementioned studies was based on the quantification of LC3B C puncta, and rather scored the overall expression level of LC3B, meaning that the evaluation criteria was rather different from those reported here.…”
Section: Discussionmentioning
confidence: 93%
“…6C) showed elevated levels of LC3B protein in R8 tumors compared with the MDA-MB-231 parental tumors, suggesting that resistant tumors also maintain higher levels of autophagy in vivo even when the selective pressure (epirubicin) is not present. Recent IHC studies have described an association between elevated expression of autophagy proteins LC3A, LC3B, and Beclin 1 in TNBC tumors compared with other molecular subtypes of breast cancer (36) and high LC3B was associated with progression and poor outcome in TNBC (37). Understanding the functional significance of elevated autophagy in different breast cancer cell types, along with the potential role and molecular mechanisms of autophagy in drug resistance, will be important areas for future study.…”
Section: Discussionmentioning
confidence: 99%
“…32,34,35,42,43 Furthermore, levels of some of these mediators are altered in diverse types of human tumors. 44,45 Based on the changes in these levels, conclusions regarding the role of autophagy in the progression of respective cancers were made. 44,45 However, some critical mediators of autophagy seem to be able to play autophagy-unrelated roles in cells.…”
Section: Introductionmentioning
confidence: 99%
“…44,45 Based on the changes in these levels, conclusions regarding the role of autophagy in the progression of respective cancers were made. 44,45 However, some critical mediators of autophagy seem to be able to play autophagy-unrelated roles in cells. For example, ATG12, one of the important stimulators of autophagosome formation, was found to cause apoptosis via physical interactions with components of the cellular apoptotic machinery (such as the BCL2 family members) in a manner independent of its ability to trigger autophagy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation